Identification of pork in raw meat using porcine-specific polymerase chain reaction assay - Khairil Mokhtar, Nur Fadhilah; Mustafa, Shuhaimi; Sazili, Awis Qurni; Nordin, Rumaisa; Che Man, Yaakob (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
The porcine-specific polymerase chain reaction (PCR) assay was developed to detect the presence of pork in raw meat either in pure or in a mixture with different meat species. A porcine-specific DNA fragment could be amplified using porcine-specific primer designed based on a porcine specific sequence of mitochondrial D-loop gene. Amplification of porcine DNA produced 174 bp porcine-specific DNA fragment and no PCR products detected when assay applied to DNA of other meat species confirming the specificity of the primers. The assay has a high potential to be employed in detection of pork in raw meat products.